Lactobacillus Protects Against S. Typhimurium–Induced Intestinal Inflammation by Determining the Fate of Epithelial Proliferation and Differentiation. Issue 5 (24th January 2020) - Lu, Xiaoxi; Xie, Shuang; Ye, Lulu; Zhu, Linda; Yu, Qinghua
Abstract : Scope: The influence of the intestinal microbiota, such as Lactobacillus, on the intestinal mucosa, particularly intestinal stem cells, remains incompletely understood. In this study, mice and intestinal organoids are used to explore the regulatory effect of Lactobacillus on the proliferation and differentiation of intestinal epithelial cells. Methods and results: This study demonstrates that S. typhimurium causes intestinal epithelial damage and affected growth of intestinal organoids. S. typhimurium also colonizes the intestine and then causes pathological changes to the intestinal epithelium, intestinal inflammation, and even death. However, L. acidophilus alleviates damage to intestinal organoids, increases the survival ratio of mice infected with S. typhimurium, and reduces tumor necrosis factor‐α (TNF‐α) secretion. Moreover, L. acidophilus affects the differentiation of epithelial cells through inhibition of the excessive expansion of goblet cells and Paneth cells induced by S. typhimurium to avoid over‐exhaustion. Finally, it is also demonstrated that L. acidophilus ameliorates overactivation of Wnt/β‐catenin pathway by Salmonella, depending on the contact with toll‐like receptor 2 (TLR2), to affect the proliferation of the intestinal epithelium. Conclusions: This study demonstrates that L. acidophilus protects the intestinal mucosa against S. typhimurium infection through not only the inhibition of pathogen invasion but also determination of the fate of the intestinal epithelium. Abstract : This study reveals that L. acidophilus ATCC 4356 modulates Wnt/β‐catenin pathway through TLR2 and affects proliferation of intestinal epithelial, as well as the differentiation of Paneth cells and goblet cells, to alleviate intestinal inflammation and crypt hyperplasia induced by S. typhimurium infection. The results suggest that besides antibiotics, L. acidophilus is also effective in curing diarrhea and improving intestinal inflammation.